Access to specialty healthcare in urban versus rural US populations: a systematic literature review - Cyr, Melissa E.; Etchin, Anna G.; Guthrie, Barbara J.; Benneyan, James C. (BMC health services research, 2019)
Background Access to healthcare is a poorly defined construct, with insufficient understanding of differences in facilitators and barriers between US urban versus rural specialty care. We summarize recent literature and expand upon a prior conceptual access framework, adapted here specifically to urban and rural specialty care. Methods A systematic review was conducted of literature within the CINAHL, Medline, PubMed, PsycInfo, and ProQuest Social Sciences databases published between January 2013 and August 2018. Search terms targeted peer-reviewed academic publications pertinent to access to US urban or rural specialty healthcare. Exclusion criteria produced 67 articles. Findings were organized into an existing ten-dimension care access conceptual framework where possible, with additional topics grouped thematically into supplemental dimensions. Results Despite geographic and demographic differences, many access facilitators and barriers were common to both populations; only three dimensions did not contain literature addressing both urban and rural populations. The most commonly represented dimensions were availability and accommodation , appropriateness , and ability to perceive. Four new identified dimensions were: government and insurance policy , health organization and operations influence , stigma , and primary care and specialist influence . Conclusions While findings generally align with a preexisting framework, they also suggest several additional themes important to urban versus rural specialty care access.